Oral health-related quality of life in women participating in the “More smiles for Chile” dental program - Henríquez-Tejo, Rocío; Chamblás-García, Isis (Revista Facultad de Odontología Universidad de Antioquia, 2020)
Introduction: oral health problems are not only a manifestation of physical problems, but they also affect psychosocial aspects. The “More Smiles for Chile” program was created to make a change on the quality of life of participating women; however, the assessments usually focus on goals achieved. The aim of the present study was to determine the oral health-related quality of life (OHRQoL) in women who participated in the “More Smiles for Chile” program at the San Pedro Family Health Center. Method: a quantitative, descriptive-correlational, cross-sectional study was conducted with a non-probabilistic sample of 120 women. The Oral Health Impact Profile (OHIP) scale and a questionnaire about demographic and dental variables were used to measure OHRQoL. The interviews were conducted at the Family Health Center. Results: the most affected components of OHRQoL are psychological discomfort and physical pain. The dimensions with significant changes in OHRQoL were: functional limitation, psychological discomfort, psychological disability, and global perception. Conclusions: the More Smiles for Chile program positively impacts the OHRQoL perception in participating women, with significant differences in post-participation averages.